ANALISIS FINANCIAL DISTRESS DENGAN MENGGUNAKAN METODE FULMER SCORE DAN ZMIJEWSKI SCORE PADA PT GOZCO PLANTATIONS, TBK - Debi Eka Putri; Nelly Ervina; Eliza Arshandy; Anggraini Syahputri (Jurnal Ilmiah Satyagraha, 2025)
This study aims to analyze the financial distress condition of PT. GozcoPlantations, Tbk using the Fulmer Score and Zmijewski Score methods anddetermine the more accurate method. The research data are secondary dataobtained from the Indonesia Stock Exchange website (www.idx.co.id). The dataanalysis techniques used are descriptive qualitative and comparative analyses. Theresults show that: First, the Fulmer Score method indicates that the company wasat risk of bankruptcy during the 2014-2023 period due to declining profits,negative operating cash flows and working capital, as well as decreased assets andequity. Second, the Zmijewski Score method indicates that the company was notat risk of bankruptcy due to reduced debts and its ability to generate profits. Third,the Fulmer Score method is more accurate in measuring bankruptcy risk, with80% of results in the danger zone compared to 20% for the Zmijewski Score.